Digital educational technology for professional nursing education at the high-school level - Fernanda dos Santos Nogueira Góes; Rosângela Andrade Aukar de Camargo; Cristina Yuri Nakata Hara; Luciana Mara Monti Fonseca (Universidade Federal de Goias, 2014)
The current study identifies what has been produced in literature regarding the use of digital educational technology for professional nursing education at the high-school level. An integrative literature review was carried out using the descriptors "Computer Assisted Instruction," "Software," "Educational Technology," "Professional Education" and "Nursing," published between 2000 and 2013. We found 99 publications, out of which 08 were analyzed. We observed that technological development has also been incorporated into nursing education, predominantly in contents regarding technical care and the use of simulations. However these were examined out of the context of their application. We also observed a gap in research about reflective education, despite the fact that a large contingent of nursing professionals is made up of assistants/technicians. The development of digital educational technology is considered a contributing factor towards professional nursing education at the high-school level, according to pedagogical principles of Brazilian curriculum guidelines and health policies. doi: 10.5216/ree.v16i2.21587.